2016
DOI: 10.1002/pds.4138
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient antidepressant drug use in children and adolescents in Germany between 2004 and 2011

Abstract: The high proportion of single prescriptions, even in patients with a diagnosed depression, and the high rate of off-label use are particularly noteworthy and should be further investigated in future studies. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 31 publications
2
27
2
1
Order By: Relevance
“…This usage pattern is not limited to North America. A recent study in Germany showed a decrease in TCA prescriptions from 0.9-0.6 prescriptions per 1000 minors [10]. This study noted the prevalence of antidepressants to be between 1.7 and 2.1 per 1000 minors and approximately 40% of the prescriptions are used offlabel.…”
Section: Discussionmentioning
confidence: 68%
“…This usage pattern is not limited to North America. A recent study in Germany showed a decrease in TCA prescriptions from 0.9-0.6 prescriptions per 1000 minors [10]. This study noted the prevalence of antidepressants to be between 1.7 and 2.1 per 1000 minors and approximately 40% of the prescriptions are used offlabel.…”
Section: Discussionmentioning
confidence: 68%
“…This can be explained by the growing share of SSRI prescriptions, especially fluoxetine. As reported previously, in 2004, fluoxetine accounted for 7.7% of all pediatric AD prescriptions in Germany. In 2006, its regulatory approval was extended to also include the treatment of moderate and severe depressive episodes in children older than 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, OLU was less common in older subjects. Imipramine, the most frequently prescribed AD during the study period, is licensed for the treatment of children from the age of 5, opipramol and sertraline from the age of 6, fluoxetine and fluvoxamine from the age of 8, and hypericum and doxepin from the age of 12. Citalopram, mirtazapine, and amitriptyline are not licensed for the use in minors at all, which explains the high proportion of prescriptions off‐label by age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many medicines already available on the market for adults continue to be used on children without appropriate studies in paediatric population and the use of unlicensed and off-label medicines in children is still a reality [4][5][6][7][8][9][10].…”
Section: Use Of Unlicensed and Off-label Extemporaneous Preparations mentioning
confidence: 99%